EFEKTIVITAS PEMANFAATAN SAMPAH PASAR SEBAGAI SUMBER ENERGI - Rullita Kinasih (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2021)
The problem vegetable waste from Pasar Mantung and the large amount of manur waste from cattle farms that are dumped into the river are the reasons for the government of Kabupaten Malang to process the waste into methane gas to produce electricity. Through the Integrated Resource Recovery Center (IRRC) development program with UNESCAP (Lorenzo Santucci, Sustainable Urban Development Section Environment and Development Division), food waste from Pasar Mantung and manure waste are processed using anaerobic biodigester to produce biogas. According to the literature, the anaerobic digestion process from food waste and cow manure is capable of producing 70% methane gas. IRRC has the potential to generate electric power of up to 100,000 KVA. However, in its operation, IRRC encountered problems where many of the vegetable waste are coated with white cement as a preservative. This affects the draining period of the biodigester unit. Based on the results of the calculations in this study, the biodigester unit in the IRRC Mantung Market needs to be drained in 2023.